2021
DOI: 10.21037/jhmhp-20-105
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for health information technologies: a systematic review

Abstract: Background: Advances in patient-facing health information technology (HIT) promise to improve health care delivery and patient outcomes. Low utilization of HIT suggests that the preferences of patients may not be adequately guiding the development of these technologies. This systematic review offers an assessment of published evidence regarding patient preferences for HIT.Methods: Articles addressing preferences for HIT from patient and other end-user groups published up through 2020 were identified from PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 98 publications
(152 reference statements)
2
1
0
Order By: Relevance
“…The initial objective of the study was to analyze Russian adults' preferences on health information resources and the utilization of digital healthcare tools. The present analysis revealed digital disparities among demographic, social, and health groups, which is in line with previously conducted studies [56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…The initial objective of the study was to analyze Russian adults' preferences on health information resources and the utilization of digital healthcare tools. The present analysis revealed digital disparities among demographic, social, and health groups, which is in line with previously conducted studies [56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…Alexander et al [30] found similar results, with the proportion of patients in an Australian hospital willing to communicate digitally instead of face-to-face being influenced by the level of concern regarding experienced symptoms, concluding that less concerned patients were more willing to use telehealth to communicate. In line with this study, several other studies also identified factors related to the patient that influence the choice for telehealth channels, such as age, gender, and education [29,31]. The identified channel-related factors in this study are also reported in other studies, showing that trustworthiness of sources and familiarization with channels influence patients' willingness to use such channels [32,33].…”
Section: Comparison With Prior Worksupporting
confidence: 88%
“…Our results are in line with previous research on factors influencing the preference for telehealth channels. A systematic review by Crossnohere et al [29] found that preference for telehealth channels is dependent on the type of problem that is communicated, with more sensitive, urgent, or complex health concerns preferably being communicated directly with a health care provider. Alexander et al [30] found similar results, with the proportion of patients in an Australian hospital willing to communicate digitally instead of face-to-face being influenced by the level of concern regarding experienced symptoms, concluding that less concerned patients were more willing to use telehealth to communicate.…”
Section: Comparison With Prior Workmentioning
confidence: 99%